Under-5 mortality due to HIV: regional levels and 1990–2009 trends. (23rd November 2010) - Stanecki, Karen; Daher, Juliana; Stover, John; Akwara, Priscilla; Mahy, Mary
Abstract : Background: Since at least the late 1990s, HIV has been viewed as a major threat to efforts by countries to reduce under-5 mortality. Previous work has documented increased under-5 mortality due to HIV from 1990 to 1999 in Africa. The current analysis presents estimates and trends in under-5 mortality due to HIV in low- and middle-income countries by region up to 2009. Methods: The analyses are based on the national models of HIV and AIDS produced by country teams in coordination with UNAIDS and its partners for the years 1990–2009. These models produce a time series of estimates of HIV-related mortality as well as overall mortality in children aged <5 years. Results and conclusion: These analyses indicate that, in 2009, HIV accounted for roughly 2.1% (1.2–3.0%) of under-5 deaths in low- and middle-income countries and 3.6% (2.0–5.0%) in sub-Saharan Africa. The percentage of under-5 deaths due to HIV has been falling in the last decade—for example, from 2.6% (1.6–3.5%) in 2000 to 2.1% (1.2–3.0%) in 2009 in low- and middle-income countries and from 5.4% (3.3–7.3%) in 2000 to 3.6% (2.0–5.0%) in 2009 in sub-Saharan Africa. This fall in the percentage of under-5 deaths due to HIV has been driven by a combination of factors including scale-up of prevention of mother-to-child transmission programmes and treatment for pregnant women and children as well as a decrease in the prevalence of HIV among pregnant women.